Medieval statecraft and the perspectives of history : essays by Joseph Strayer - Strayer, Joseph R. (Joseph Reese), 1904-1987.; Benton, John F.; Bisson, Thomas N.; Post, Gaines, 1902-1987 (Princeton : Princeton University Press, 2015)
This collection of essays by the eminent historian Joseph Strayer makes available in one volume his important shorter studies on the central theme of the political, constitutional, and institutional history of France and England in the twelfth and thirteenth centuries. Originally published in 1971.
I. Normandy ; The writ of novel disseisin in Normandy at the end of the thirteenth century -- Economic conditions in the county of Beaumont-le-Roger, 1261-1313 -- A forged charter of Henry II for Bival -- On the early Norman charters, 911-1066 -- Normandy and Languedoc -- II. Feudalism ; The two levels of feudalism -- The development of feudal institutions -- The Tokugawa period and Japanese feudalism -- III. Crusades ; The crusade against Aragon -- The political crusades of the thirteenth century -- The crusades of Louis IX -- IV. Philip the Fair ; Philip the Fair-a "constitutional" king -- Viscounts and viguiers under Philip the Fair -- Pierre de Chalon and the origins of the French customs service -- Italian bankers and Philip the Fair -- V. Problems of state-building ; The laicization of French and English society in the thirteenth century -- The statute of York and the community of the realm -- Defense of the realm and royal power in France -- France : the Holy Land, the chosen people, and the most Christian king -- The promise of the fourteenth century -- The state and religion : an exploratory comparison in different cultures -- Empires : some reflections on Roman and modern imperialism -- The first western union -- The historical experience of nation-building in Europe -- Problems of dictatorship : the Russian experience -- VI. The teaching of history ; Introduction to "The Interpretation of History" -- United States history and world history -- The teaching of world cultures : a historian's viewpoint -- Graduate training in the humanities.
Festschrift for J.R. Strayer.
Edited by John F. Benton and Thomas N. Bisson -- Cover.
Includes chronological bibliography of works by Joseph R. Strayer (pages 401-410), and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Strayer, Joseph R. -- 1904-1987 -- Bibliography; Strayer, Joseph R. -- 1904-1987; Middle Ages -- Historiography; Constitutional history, Medieval; Moyen Âge -- Historiographie; Histoire constitutionnelle médiévale.; LITERARY CRITICISM -- Medieval; HISTORY -- World; Constitutional history, Medieval; Middle Ages -- Historiography; Bibliographies